Role of acetylation in nonalcoholic fatty liver disease: a focus on SIRT1 and SIRT3 - Fatiha Nassir (Open Exploration Publishing Inc., 2020)
Nonalcoholic fatty liver disease (NAFLD) has become the most prevalent liver chronic disease worldwide. The pathogenesis of NAFLD is complex and involves many metabolic enzymes and multiple pathways. Posttranslational modifications of proteins (PMPs) added another layer of complexity to the pathogenesis of NAFLD. PMPs change protein properties and regulate many biological functions, including cellular localization, stability, intracellular signaling, and protein function. Lysine acetylation is a common reversible PMP that consists of the transfer of an acetyl group from acetyl-coenzyme A (CoA) to a lysine residue on targeted proteins. The deacetylation reaction is catalyzed by deacetylases called sirtuins. This review summarizes the role of acetylation in NAFLD with a focus on sirtuins 1 and 3.